Case Study of Stunting Toddlers in Paluh Manis Village, Kecamatan Gebang Kabupaten Langkat - Jamilah, Jamilah; Hidayat, Wisnu; Tarigan, Frida Lina (Sari Mutiara Indonesia University Press, 2018)
Objective: The purpose of the study was to determine and analyze the factors that cause stunting in children under five (a case study of stunting toddlers in Paluh Manis Village, Gebang District, Langkat District, 2018). Background: Stunting is a failure to grow in toddlers (infants under five years) due to chronic malnutrition so that the child is too short for his age. Factors that cause stunting in children under five include family and household factors, factors of inadequate supplementary feeding, inappropriate breastfeeding practice factors and clinical and subclinical infection factors. Methods: Qualitative research designed with phenomenological study designed by taking 9 informants. Data collection used interview guidelines and the researchers as data collectors conducted from January to July 2018. Results: The results showed that the causes of stunting in toddlers (case study of stunting toddlers in Paluh Manis Village, Gebang District, Langkat District, 2018) were economic factors and factors lack of knowledge. Conclusion: Researchers suggest that local governments should be active in programs to deal with stunting toddlers such as supplementary feeding programs and counseling to stunting mothers of toddlers with home visits and adding nutrition health workers to help with stunting prevention.